PERAN HEREDITAS DAN LINGKUNGAN MENJADI FONDASI UTAMA DALAM PERKEMBANGAN MANUSIA - Ardelia Salsabilla; Muhammad Nur Teguh Utomo; Nadya Kamilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Human development is influenced by two inseparable main foundations: heredity and environment. Heredity serves as the biological basis that determines an individual's initial potential through genetic inheritance, while the environment serves as a means to determine the extent to which that potential can develop optimally. This study applies a descriptive qualitative approach based on liberal research by examining three main schools of development: nativism, empiricism, and convergence theory. The results of the study indicate that convergence theory is the most realistic approach because it emphasizes that individual development is the result of a synergistic interaction between innate and environmental factors on an ongoing basis. Therefore, optimal human development can only be realized if good hereditary potential is supported by a conducive and quality environment.